Somatic Embryo Germination of Jatropha curcas L in Presence of Sucrose and Poly Ethylene Glycol (PEG) - Rudiyanto Rudiyanto; Darda Efendi; Tri Muji Ermayanti (ANNALES BOGORIENSES, 2014)
Jatropha curcas L. is a potential source of a non-edible biofuel. Conventional propagation of J. curcas technique has some limitations. Somatic embryo can produce a large number of embryos and obtain a large number of plants all year round. Treatment of sucrose in combination with polyethylene glycol (PEG) was proven to enhance germination of somatic embryos in many plant species. The aim of the study was to investigate the effect of sucrose in combination of PEG on somatic embryo germination in J. curcas. Globular somatic embryos at 0.025-0.030 g fresh weight having 0.4-0.5 cm in diameter were grown on MS medium solidified with 3 g/l of Gelzan supplemented with sucrose at 20, 30, 40, and 50 g/l in combination with PEG at 0, 2.5, 5, 10, and 15%. Results showed that the best medium for germination of J. curcas somatic embryo cultures was MS medium supplemented with 20 and 30 g/l of sucrose in combination with 5% of PEG. The numbers of germinated embryos per clump had significant enhancement on those medium compared with the control (PEG free treatment) (2.65 to 5.65) and (2.55 to 5.50). In addition, those treatments resulted in the highest percentage of clumps forming germinated embryos (100%), with an average of normal germinated embryos at 94.163 and 96.065%. The addition of 40 and 50 g/l of sucrose in combination with 15% of PEG caused all embryos to fail at germinating.